“…noxiousness of my work:” Miroslav Macháček’s 1971 "Henry V" at the Normalized National Theatre - Pšenička, Martin (Multicultural Shakespeare: Translation, Appropriation and Performance, 2023)
The essay focuses on the 1971 production of William Shakespeare’s rarely staged historical drama Henry V, directed by Czech director Miroslav Macháček at the Prague National Theatre in a new translation by Czech literary historian and translator Břetislav Hodek. Macháček staged the play shortly after the 1968 occupation of Czechoslovakia by Warsaw Pact troops. The premiere of the play provoked negative reactions from influential Communist officials, including the leading post-1968 politician Vasil Biľak. Macháček’s performance, which, in the director’s words, was intended as a universal anti-war parable, became a political topicality that the newly emerging normalisation authorities understood as a deliberate political, anti-socialist provocation. The essay traces the background of the production, including the translation of the play, and the consequences of the staging for Macháček. At the same time, it attempts to unravel a number of ambiguities and ambivalences associated with the period of normalization (1970s and 1980s) and its research. A special focus is given to the production itself as it disturbed the audience with its ambivalence. In this analytical section, the essay works with Norman Rabkin’s conception of Henry V, as presented in his essay “Rabbits, Ducks, and Henry V,” which traces Shakespeare’s complex grasp of the historical figure and the events associated with Henry. Macháček, who staged the play several years before this essay by Rabkin, pursued similar intentions with his stage concept. It was this unsettling ambivalence that carried within it the features of both a parable and a political gesture that spoke out against the communist occupation.